Photocatalytic C-H functionalization of nitrogen heterocycles mediated by a redox active protecting group - Pizzio, Marianela G. (2023)
Fil: Fil: Pizzio, Marianela G. Université Paris Saclay. Institut de Chimie des Substances Naturelles; France.